ROLE OF MATERIALS DEVELOPMENT FOR ENGLISH LANGUAGE LEARNING AND TEACHING - Tashkhodjayeva Umida Khasanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the role of materials development for English language learning and teaching in the field of pedagogy and its importance in foreign language teaching. At the same time, the article analyzes the peculiarities of the choice of materials and their use in foreign language teaching.